VULNERABILITY ASSESSMENT OF BLAST WALLS OF OFFSHORE STRUCTURE UNDER ACCIDENTAL EXPLOSION - Abdul Rahim, Mohamad Najib (Universiti Teknologi PETRONAS, 2013)
Blast walls are provided in offshore structures for protecting critical structural components and personnel on offshore structure from accidental explosions. This study investigates the vulnerability of blast walls under different blast loading conditions. Although blast is a low probability event but can have devastating effect on an offshore structure and on the personnel working on it. Blast wall acts as a barrier to avoid the high magnitude of blast to affect the other parts of the structure like what happen in the Alpha Oil rig. Currently, there is no exact and well accepted guideline to design blast walls for offshore structures due lack of proper investigation on the structural response and vulnerability of blast walls under different blast loadings. Therefore, this research studies the structural response and vulnerability of blast walls to gain in-depth detailed response of blast walls under different blast loading. This study consists of 4 major elements which are the modelling, study of response, investigation on vulnerability and recommendations for design. The findings of this research are expected to help effective and economic design of blast walls for better protection. The results show that today’s blast wall design is very vulnerable to blast overpressure exceeding 10 MPa because 10 MPa of blast overpressure will cause the blast wall to deform to more than 0.5 m. The deformation pattern also can be seen that the middle part of the blast wall is the most crucial part of the structure since it has the highest deformation compared to the other part of the blast walls.